TINJAUAN YURIDIS KEDUDUKAN MAKELAR DALAM PERJANJIAN PENGANGKUTAN BARANG DENGAN KAPAL LAUT DI PELABUHAN PALARAN SAMARINDA - Devi Octavia (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThe title of this thesis is Juridical Position Overview Realtor In Agreement With Transport Cargo Ship In Port Palaran Samarinda. Our country has been awarded by the grace of God Almighty, an archipelago consisting of thousands upon thousands of islands, located aft underlined the equator between two continents and two oceans, therefore the state of Indonesia has a strategic position in the relations between nations.Transporting or transportation is a means to accelerate the economy, strengthen national unity and strengthen the relationship between the state, the importance of the transport is reflected in the implementation of development that affects all aspects of life of the nation and state, and the increasing need for transportation services for the mobility of people and goods within the country as well as to and from abroad. For the purposes of the business of each entrepreneur freight transport will be attempted to obtain continuous and high and low transportation costs, for all this required traffic regulations by land, sea, or air. Broker is an intermediary that connects entrepreneurs with the users of transport services to an agreement, In agreement by sea, there are three parties which have a relationship of mutual relation to one another.The research is juridical normatife and juridical empirical consisting of primary legal materials, legal materials secondary and tertiary legal materials, the legal research of this type, often laws are drafted as what is written in the regulations Legislation (law in books) or conceptualized as a legal rule or norm that is the benchmark of human behavior is considered appropriate. In addition to research resources in the form of legal materials, legal research can also use material non-legal, if deemed necessary, namely in the form of books on the science of Politics, Economics, Sociology, Philosophy, Culture or reports research is non - the law made in the field by means of questionnaires or interviews with sources and journals all have relevancy to the research topic.According to Article 62 Kitap Law - Commercial Law broker is a middleman appointed by the president has been declared competent authority. He organized his company to do the work, as referred to in Article 64, as they received wages or certain peropesi, on the mandate and the names of people with whom he did not have a stable relationship. In every relationship of cooperation, each party certainly do not want a loss that befell them. Because in principle every cooperation forged in the expected profit for each party. So is the case in cooperation between a broker by consumers as users of services in the field of transport by ship.Realtor in performing their duties must pay attention to the rights of consumers as users of services, because the broker will be accountable for their work to consumers. Because if the realtor can not do a good job, of course, his reputation as a realtor is going down and not even rule out the possibility he would be sued because it has been in default (broken promises). Broken promise is meant here is the lack of incapacity broker as an intermediary for the consumer to take care of the transport by ship which they had of the agreement.To the public or businesses engaged in trade, who want their goods to their destination faster then it's good to use the services of a realtor to look for and take care of and looking for a company to transport the goods to be sent. Keywords: Brokerages Port Palaran Samarinda